Developing web services security systems: a case study. (21st July 2006) - Fernandez-Medina, Eduardo; Gutierrez, Carlos A.; Piattini, Mario
This article presents a case study in which the PWSSec (Process for Web Services Security) process was applied in the development of a web services-based system. It deals with the migration of an existing system whose objective is the execution of a workflow that enables web customers to carry out payments from their account to the account of a web-based organisation. Throughout this article, we present the difficulties encountered when applying the PWSSec, as well as the solutions that were employed. Some of these solutions were developed from scratch and others were adapted from existing proposals found in current literature.